Implementasi BIM terhadap Upaya Pengurangan Waste Material Konstruksi pada PT. Wijaya Karya Jabodetabek - fauziyah, shifa (Civil Infrastructure Engineering and Architectural Design, 2023)
In the implementation of construction projects, materials are a very influential component in determining the cost of a project. Residual material causes wastage and reduces project profits. Research is needed to analyze the implementation of Building Information Modeling (BIM) in efforts to minimize construction material waste. The population of the research is WIKA employees who have implemented BIM in the Jabodetabek area (Jakarta, Bogor, Depok, Tangerang and Bekasi). The research sample was 100 people. The data is processed using the Smart PLS software. The results showed that the implementation of BIM had a positive and significant effect on efforts to reduce residual construction materials. If the implementation of BIM is applied with discipline, stakeholders will have a more complete data source for estimating material needs.